International ethics concepts, theories, and cases in global politics - Amstutz, Mark R. (Lanham Rowman & Littlefield, 2018)
Mark Amstutz illustrates the role of moral norms in global politics and the ethical foundation of the rules, institutions, and structures of global society with twenty-six new and revised case studies, including the ethics of climate change, the refugee crisis, and the Syrian civil war. The cases address the following major global issues: human rights, war, unconventional military operations, foreign intervention, international economic relations, justice among states, and global justice. This comprehensive study will be of special interest to students and practitioners of international affairs who are concerned with the role of political morality and ethical judgment in global affairs.
Includes bibliographical references and index.
Keywords: International relations--Moral and ethical aspects